Genetic diversity of french bean (Phaseolus vulgaris L.) under water stress condition (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 25-30